Gamma4: a genetically versatile Gammaproteobacterial nifH phylotype that is widely distributed in the North Pacific Ocean. (27th May 2021) - Cheung, Shunyan; Zehr, Jonathan P.; Xia, Xiaomin; Tsurumoto, Chihiro; Endo, Hisashi; Nakaoka, Shin‐ichiro; Mak, Wingkwan; Suzuki, Koji; Liu, Hongbin
Summary: Despite the increasing reports of non‐cyanobacterial diazotrophs (NCDs) in pelagic waters, only one NCD (GammaA) has been relatively well described, whose genome and physiology are still unclear. Here we present a comprehensive analysis of the biogeography and ecophysiology of a widely distributed NCD, Gamma4. Gamma4 was the most abundant Gammaproteobacterial NCD along transects across the subtropical North Pacific. Using quantitative PCR, Gamma4 was detectable throughout the surface waters of North Pacific (7°N–55°N, 138°E–80°W), whereas GammaA was detected at <2/3 of the stations. Gamma4 was abundant during autumn‐winter and positively correlated with chlorophyll a, while GammaA thrived during spring‐summer and was positively correlated with temperature. Environmental clones affiliated with Gamma4 were widely detected in pelagic waters, oxygen minimum zones and even dinoflagellate microbiomes. By analysing the metabolic potential of a genome of Gamma4 reconstructed from the Tara Oceans dataset, we suggest that Gamma4 is a versatile heterotrophic NCD equipped with multiple strategies in scavenging phosphate (and iron) and for respiratory protection of nitrogenase. The transcription of nitrogenase genes is putatively regulated by Fnr‐NifL‐NifA and GlnD‐GlnK systems that respond to intracellular oxygen and glutamate concentration. These results provide important implications for the potential life strategies of pelagic NCDs.